Occupational Burnout and its Relation to Academic Staff Performance at Al Ain University, college of education (evaluation study) - Suad Abdelkareem Alwaely (International Journal of Cognitive Research in Science, Engineering and Education, 2020)
This study aims to identify the occupational burnout and its relation to teaching performance among Al Ain University (AAU) academic staff. The sample of the study consisted of 60 male and female teachers of Al Ain University First Directorate of Education. The researchers designed two tools for the study, represented in occupational burnout questionnaire for teachers and teaching performance questionnaire. The results show that teachers in the education college in AAU have a moderate level of occupational burnout. There are differences in the occupational burnout level for the favor of females, and differences in teaching experience for the favor of 10 years and more. The researchers ascribe this result to increased workloads and stress that female teachers face. Female teachers are more exposed to occupational burnout than male teachers because female teachers also face loads in connection with household and family concerns. There is as well an inverse relationship with statistical differences between occupational burnout level for teachers and their performance level. The study results in many recommendations and suggestions.